Bobcat Predation on Quail, Birds, and Mesomammals - Michael E. Tewes; Jennifer M. Mock; John H. Young (National Quail Symposium Proceedings, 2017)
We reviewed 54 scientific articles about bobcat (Lynx rufus) food habits to determine the occurrence of quail, birds, and mesopredators including red (Vulpes vulpes) and gray fox (Urocyon cinereoargenteus), raccoon (Procyon lotor), skunk (Mephitis spp.), and opossum (Didelphis virginianus). Quail (Colinus virginianus, Cyrtonyx montezumae, Callipepla squamata, C. gambelii, C. californica, Oreortyx pictus) were found in 9 diet studies and constituted 3% of the bobcat diet in only 2 of 54 studies. Birds occurred in 47 studies, but were also a minor dietary component in most studies. Although mesopredators were represented as bobcat prey in 33 of 47 studies, their percent occurrence within bobcat diets was low and showed regional patterns of occurrence. Bobcats are a minor quail predator, but felid effects on mesopredators and secondary impacts on quail need to be studied.
Keywords: bobcat; California quail; Callipepla californica; C. gambelii; C. squamata; Colinus virginianus; Cyrtonyx montezumae; depredation; diet; food habits; Gamble’s quail; Lynx rufus; mesomammal; mesopredator; Montezuma quail; mountain quail; northern bobwhite; Oreortyx pictus; scaled quail